2007
DOI: 10.1097/bcr.0b013e318031a1d1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Serum Lactate and Base Deficit in Burn Patients to Mortality

Abstract: Serum lactate and base deficit in trauma patients have been shown to correlate with mortality. This study examines the relationship of these parameters to mortality among burn patients. We evaluated patients with >or=20% TBSA burn injury who had a serum lactate or base deficit recorded during the initial 48 hours of admission over a 5-year period. The primary study outcome was mortality. The mean (+/-SD) age of study patients (N = 128) was 35.2 +/- 21.1 years, the mean burn size was 41.7 +/- 17.9% TBSA, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Hyperlactatemia is an independent risk factor for the mortality of burn patients 7 . Over and above hypoperfusion and subsequent tissue hypoxia, a metabolic shift from mitochondrial oxidative phosphorylation to ATP synthesis by glycolysis in the presence of sufficient oxygen availability has been proposed to contribute to hyperlactatemia in critical illnesses, such as sepsis and burn injury 9–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlactatemia is an independent risk factor for the mortality of burn patients 7 . Over and above hypoperfusion and subsequent tissue hypoxia, a metabolic shift from mitochondrial oxidative phosphorylation to ATP synthesis by glycolysis in the presence of sufficient oxygen availability has been proposed to contribute to hyperlactatemia in critical illnesses, such as sepsis and burn injury 9–13 .…”
Section: Introductionmentioning
confidence: 99%
“…In case of circulatory failure, such as severe sepsis, lactate concentration is a complex result of an anaerobic production, an aerobic production via the Na-K ATPase channel, and a decrease in lactate utilization [8-11]. However, several studies have described a correlation between baseline lactate concentration and mortality of ICU patients [12-15]. Although informative for severity assessment of septic patients, basal lactate rate is useless to guide therapy of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cartotto et al19 have shown that a 24-hour BD < −6 was associated with a greater degree of systemic inflammatory response syndrome, ARDS, and MODS. Similarly, Cochran et al20 have shown BD and lactate values in the first 24 hours to be significantly worse in nonsurvivors. This is similar to other burn studies, which have shown elevated BDs to be associated with more extensive burns, inhalation injuries, higher than anticipated fluid requirements, and an increased risk of death 21–23.…”
Section: Discussionmentioning
confidence: 83%